Editor Profile: Karl Forchhammer. (6th December 2021) - ,; Forchhammer, Karl
Abstract : In this special interview series, we profile members of The FEBS Journal editorial board to highlight their research focus, perspectives on the journal and future directions in their field. Since 2007, Karl Forchhammer is the director of the Department of Microbiology/Organismic Interactions in the University of Tübingen. He has served as an editorial board member of The FEBS Journal since 2008. Abstract : In this special interview series, we profile members of The FEBS Journal editorial board to highlight their research focus and perspectives on the journal and future directions in their field. Since 2007, Karl Forchhammer is the director of the Department of Microbiology/Organismic Interactions in the University of Tübingen. He has served as an editorial board member of The FEBS Journal since 2008.